Pengaruh Penerapan Tax Amnesty Terhadap Penerimaan Pajak (Jurnal Kendali Akuntansi, 2024)
This study aims to review previous research information because the idea of the implementation of tax amnesty in Indonesia is still developing and serves as a basis for scientific development and can provide ideas on new topics in the future. This study used a systematic literature review (SLR), and 37 SINTA-accredited articles were evaluated. The number of publications related to tax amnesty is constantly changing from 2018 to 2024. The most common research method is qualitative research, and several articles published from 2018 to 2024 will be systematically analyzed. In contrast, tax revenues are significantly affected by Tax Amnesty measures. This is in accordance with the purpose of Tax Amnesty, which is to increase tax revenue, which among other things will be used to finance development. Overall, research on the implementation of tax amnesty in Indonesia has been quite good, but it needs to be improved due to the lack of researchers, lack of knowledge about taxes, and limited discussion topics.